PAPEL DA HIDROGINÁSTICA NA CAPACIDADE FUNCIONAL DE IDOSOS - ROLE OF HYDROGYMNASTIC IN THE FUNCTIONAL CAPACITY OF ELDERLY - Iransé Oliveira-Silva; Larissa Rafaella Bardella Arcanjo (UniEVANGÉLICA, 2017)
Objective: To present the influence of a hydrogymnastic (water aerobics) program on the functional capacity of elderly women. Methods: With a sample of 60 elderly women with mean age of 65.9 ± 3.2 years, subdivided into two groups: 30 hydrogymnastic practitioners and 30 sedentary. For this study was applied the test of Rikli and Jones (2008), which consists of a set of tests that allow to evaluate the functional capacity of the elderly. The software SPSS for Windows version 22.0 was used, and the significance level adopted was p ≤ 0.05. Results: It was evidenced that the elderly women attending hydrogymnastic classes over 6 months had higher levels of functional capacity in all battery tests compared to sedentary women (p=0.01). Conclusions: An program of hydrogymnastic in more than six months has positively influences the functional capacity of the elderly. However, it is recommended to include strength exercises to minimize the losses of this component as the age advances